2012
DOI: 10.1136/bmjspcare-2012-000264.26
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and medical care after bereavement: a general practice cohort study

Abstract: Bereaved spouses or partners are thought to be at increased risk of morbidity and mortality. However, there are few large prospective studies and results are inconsistent. We estimated the relative mortality, prescription of psychotropic medication and use of primary medical care services in adults whose cohabitee died of cancer. To do this, we undertook a cohort study using The Health Improvement Network (THIN) UK primary care database. Participants were 1) people aged over 40, who were registered with genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Furthermore, family members who care for a dying relative suffering from cancer are bur- interviewed bereaved caregivers of cancer patients and found that the experience of waiting and watching while a loved one dies without being able to do anything about it was characterised by shock and distress (Sanderson et al, 2013). The release from the stress of caring may lead to reduced psychological distress for caring relatives as the acute phase of grief subsides (King et al, 2013). The death of a close one can be traumatising, no matter how well families are prepared and symptoms are managed (Sanderson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, family members who care for a dying relative suffering from cancer are bur- interviewed bereaved caregivers of cancer patients and found that the experience of waiting and watching while a loved one dies without being able to do anything about it was characterised by shock and distress (Sanderson et al, 2013). The release from the stress of caring may lead to reduced psychological distress for caring relatives as the acute phase of grief subsides (King et al, 2013). The death of a close one can be traumatising, no matter how well families are prepared and symptoms are managed (Sanderson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Given that neither material circumstances, nor access to health care, appear to be protective[6, 7], psychological and lifestyle factors may well play a key role. Our earlier analyses using the THIN database demonstrated that bereaved widows and widowers were about twice as likely to be prescribed hypnotics or antidepressants, even after adjustment for levels of such prescribing before the partner’s death[11]. It has long been thought that the emotional stress of bereavement might be part of the mechanism of increased mortality in bereavement[21] through changes in pulse rate, arterial blood pressure and endocrine function.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, however, there is evidence that reduced health care for cardiovascular disease before and after bereavement may play a role[8]. However, not all prospective studies agree on the findings[4, 911], possibly because of the difficulties of finding appropriate comparison cohorts and because of confounding. Research into whether death of a spouse or partner increases morbidity and mortality in older people has yielded conflicting results[4, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations